Leaf anatomical characters of four epiphytic orchids of Sempu Island, East Java, Indonesia: The importance in identification and ecological adaptation - RIDESTI RINDYASTUTI; SITI NURFADILAH; APRIYONO RAHADIANTORO; LIA HAPSARI; ILHAM KURNIA ABYWIJAYA (Society for Indonesian Biodiversity, 2018)
Rindyastuti R, Nurfadilah S, Rahadiantoro A, Hapsari L, Abywijaya IK. 2018. Leaf anatomical characters of four epiphytic orchids of Sempu Island, East Java, Indonesia: The importance in identification and ecological adaptation. Biodiversitas 19: 1906-1918. Leaf anatomy features are important characters to support species identification and classification, and they are related to ecological adaptation of species. The aims of the present study were: (i) to investigate leaf anatomical characters of four epiphytic orchids of Sempu Island (Ascochilus emarginatus, Dendrobium subulatum, Thrixspermum subulatum, and Thrixspermum acuminatissimum) in relation to the significance in species identification and ecological adaptation in coastal habitats of Sempu Island, (ii) to compare the adaptive ability of the four species in coastal habitats based on adaptive anatomical characters. The procedure of leaf anatomical studies as follows: orchid leaves were fixed in ethanol 70% and sliced into thin pieces with a microtome, and stained with 1% Safranin. The leaf anatomical organization of orchids (stomata, epidermis, mesophyll, vascular bundles, and other characters such as hypodermis, fibre bundles, raphide bundles, and spiral thickenings) was observed under light microscope. The results showed the comparable data of leaf anatomical characters among the orchids. There was distinct variation in the anatomical characters of the orchids including stomata anomocytic, tetracytic, and cyclocytic; the presence or absence of hypodermis, spiral thickenings, fibre bundles, raphide bundles, and bundle sheaths; homogenous and heterogenous mesophyll; and variation in vascular bundle arrangement. Detailed leaf anatomical characters can be used to distinguish a species from others, which are important to support species identification. The similarity of anatomical characters among these orchids were they possessed relatively thick cuticle and other specific anatomical characters as a structural adaptation to coastal habitat with high irradiation to reduce leaf transpiration. D. subulatum can be considered as the most adaptive orchid species to coastal habitats based on adaptive anatomical characters as it possessed the largest number of adaptive anatomical characters. The implication of this study is the importance of leaf anatomical features to support species identification and to increase understanding of orchid biology and ecology which are important in orchid conservation.